Email: a challenge to information management - Badilla Marín, Ricardo (2024)
This article aims to analyze email from its origin to considering it an archival document within public institutions. This will be achieved through an exploratory, descriptive methodology and from an archival perspective that allows it to be classified as an archival document based on its characteristics of authenticity, integrity, reliability and availability. The challenge represented by the use and management of emails within the institutions that belong to the National Archives System of Costa Rica will be addressed. By classifying them as records, a starting point is established to ensure that the management and storage of emails is optimal, considering these elements as records of communication in an organization or between individuals. These provide a valuable source of information and evidence in legal and administrative contexts within public institutions. Furthermore, in the digital age, emails have become an essential communication tool in organizations, which increases their relevance by containing critical information for decision making, which is why managing them as archival documents is the best choice.